Examining the dimensionality of morphological knowledge and morphological awareness and their effects on second language vocabulary knowledge - Wang, Tuoxiong; Zhang, Haomin (Frontiers in Psychology, 2023)
Morphological knowledge and morphological awareness are multidimensional and both have been confirmed to make important contributions to vocabulary knowledge. However, the extant literature has not made a clear demarcation between morphological knowledge and morphological awareness. The current study examined the underlying components of morphological knowledge and morphological awareness as well as their effects on vocabulary knowledge. The performance of 226 tenth- and eleventh-graders on five tasks was investigated using confirmatory factor analysis and structural equation modeling. Results demonstrated that morphological knowledge and morphological awareness were two distinct constructs. In regard to the direct and indirect effects between morphological knowledge and vocabulary, it was indicated that morphological knowledge made a significant indirect effect on vocabulary knowledge through morphological awareness. However, the direct effect of morphological knowledge on vocabulary knowledge was not significant. Findings from the current study have important implications to adolescent EFL students’ vocabulary instruction and research.